A long-term ichthyoplankton monitoring program suggests climate-induced environmental variabilities changed fish communities in the Hudson River estuary - Chang, Hsiao-Yun; McKown, Kim; Chen, Yong (Frontiers in Marine Science, 2023)
Climate change is known to have significant impacts on coastal marine ecosystems. However, a good understanding of the exact impacts requires consistent long-term monitoring programs, which are not available for many coastal marine ecosystems. The Hudson River Estuary (HRE) provides critical habitats for many estuarine, freshwater, and diadromous species. The Longitudinal River Ichthyoplankton Survey and Water Quality Survey in the Hudson River Biological Monitoring Program provided a long-term time series (1974-2017) for examining the changes in salinity and other environmental variables and identifying the temporal variability of fish diversity. In this study, we examined the environmental data and found a 2-phase pattern in the salinity time series data with a change point of 1984. We calculated a Margalef index and a Simpson index to examine species richness and evenness for early and older life stages in the upper and lower HRE, and explored the potential effects of rising sea level and salinity on fish biodiversity. This study reveals that sea level and salinity may play an important part in explaining increased species richness and evenness. The increased occurrence, establishment and range expansion of marine species as well as possible displacement of freshwater species may be associated with sea level-induced salinity change observed in the HRE. This study highlights a need for a long-term consistent monitoring program and a better understanding of climate change effects on the biota in coastal estuary ecosystems such as the HRE in order to enhance management, conservation, and restoration plans.